Divalproex sodium modulates nuclear localization of ataxin‐3 and prevents cellular toxicity caused by expanded ataxin‐3. (9th January 2018) - Wang, Zi‐Jian; Hanet, Aoife; Weishäupl, Daniel; Martins, Inês M.; Sowa, Anna S.; Riess, Olaf; Schmidt, Thorsten
Summary: Background & Aims: Spinocerebellar ataxia type 3 (SCA3), also known as Machado‐Joseph disease (MJD), is an autosomal dominantly inherited neurodegenerative disorder and the most common form of SCA worldwide. It is caused by the expansion of a polyglutamine (polyQ) tract in the ataxin‐3 protein. Nuclear localization of the affected protein is a key event in the pathology of SCA3 via affecting nuclear organization, transcriptional dysfunction, and seeding aggregations, finally causing neurodegeneration and cell death. So far, there is no effective therapy to prevent or slow the progression of SCA3. Methods: In this study, we explored the effect of divalproex sodium as an HDACi in SCA3 cell models and explored how divalproex sodium interferes with pathogenetic processes causing SCA3. Results: We found that divalproex sodium rescues the hypoacetylation levels of histone H3 and attenuates cellular cytotoxicity induced by expanded ataxin‐3 partly via preventing nuclear transport of ataxin‐3 (particularly heat shock‐dependent). Conclusion: Our study provides novel insights into the mechanisms of action of divalproex sodium as a possible treatment for SCA3, beyond the known regulation of transcription.